Novel Therapies in Primary Central Nervous System Lymphoma - Wakim M; Mezher M; Perez-Perez A; Maharaj A; Odia Y; Ahluwalia MS; Linhares Y (Clinical Pharmacology: Advances and Applications)
Michel Wakim,1,* Mariana Mezher,2,* Ariel Perez-Perez,3 Arun Maharaj,3 Yazmin Odia,3 Manmeet S Ahluwalia,1,3 Yuliya Linhares1,3 1Herbert Wertheim College of Medicine, Florida International University, Miami, FL, USA; 2Faculty of Medical Sciences, Lebanese University, Beirut, Lebanon; 3Miami Cancer Institute, Baptist Health South Florida, Miami, FL, USA*These authors contributed equally to this workCorrespondence: Yuliya Linhares, Translational Medicine, Florida International University, Chief of Lymphoma Services, Miami Cancer Institute, 8900 N Kendall Dr, Miami, FL, 33176, USA, Tel +1-310-795-6849, Email yuliyal@baptisthealth.netAbstract: Primary central nervous system lymphoma (PCNSL) is a rare, aggressive, extranodal lymphoma exclusively located in the central nervous system. High-dose methotrexate (HD-MTX)-based chemotherapy combination regimens are now the standard of care for the upfront treatment of PCNSL and are used in a salvage setting but are toxic and cumbersome to administer because of the need for inpatient supportive care. While the incidence of PCNSL is increasing in the aging population, a significant proportion of patients are unable to follow HD-MTX protocols owing to performance status and organ dysfunction. Consolidative autologous stem cell transplant or whole-brain radiation therapy improves progression-free survival at the cost of short- and long-term toxicities. Induction of low toxicity and consolidative and salvage therapeutic options are lacking. Due to its unique biology, PCNSL presents an exciting opportunity for the development of novel therapies with improved efficacy and toxicity. In this review, we focus on the biology of PCNSL and novel chemotherapeutics, including targeted and immunotherapeutic agents as well as cellular therapies. Expert Opinion summary: Given the lack of low-toxicity standard treatments for PCNSL, the outcomes for aging PCNSL patients remain suboptimal. Current research has focused on introducing targeted immunotherapies into the induction, salvage, and consolidation treatments of PCNSL.Keywords: primary central nervous system lymphoma (PCNSL), high-dose methotrexate (HD-MTX) in PCNSL, targeted therapy in PCNSL, immunotherapy in PCNSL, Bruton tyrosine kinase (BTK) signaling pathway in PCNSL, chimeric antigen receptor T cells (CARTs) in PCNSL